Application of vacuum arc deposition surface structural materials (International Journal of Mathematics and Physics, 2016)
This paper presents experimental results of plasma flow impact on the surface of various materials. Using pulsed plasma generated by vacuum arc accelerator, managed to get a copper protective coating on the surface of materials, such as tool steel, carbon steel and aluminum. Treatment of test materials was carried out at various modes of plasma exposure. To demonstrate the deposition process, the paper presents the virtual model of the physical laboratory simulating the creation of the coating. This model allows analyzing this process, to control every stage of the plasma treatment and forms the basis for automation of the proposed deposition technique.   GMT АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский        Звуковая функция ограничена 200 символами  Настройки : История : Обратная связь : DonateЗакрыть